Apolipoprotein B Discordance with Low-Density Lipoprotein Cholesterol and Risk of Atherosclerotic Cardiovascular Events and Mortality: A Systematic Review and Meta-Analysis - Adinda Wafdani Putri; Jessica Adrya; Srigita Varsha; Muhammad Ferhat; Stella Pangestika; Natania Eliadi; Alan Dharmasaputra (Medicinus, 2026)
Background: Apolipoprotein B (apoB) reflects the burden of atherogenic lipoprotein particles and may identify residual cardiovascular risk when low-density lipoprotein cholesterol (LDL-C) or non-high-density lipoprotein cholesterol appears controlled. This review evaluated whether elevated apoB discordance is associated with cardiovascular events and mortality. Methods: PubMed, Scopus, ScienceDirect, and Google Scholar were searched through 23 May 2026. Eligible studies enrolled adults, assessed apoB discordance using residual-, percentile-, or median-based definitions, and reported adjusted estimates for clinical outcomes. Risk of bias was assessed using the Newcastle-Ottawa Scale. Random-effects meta-analysis used restricted maximum likelihood estimation with Hartung-Knapp-Sidik-Jonkman adjustment. Result: Four studies (128,103 participants) were included. In the cohort-only analysis, the pooled estimate was HR 1.28 (95% CI 0.31-5.25; I² = 67.7%). For all-cause mortality, the pooled estimate was HR 1.12 (95% CI 1.02-1.23; I² = 0%). The residual-based excess apoB-only analysis showed HR 1.11 (95% CI 1.04-1.17; I² = 0%). Conclusions: ApoB discordance may identify residual risk beyond LDL-C, with the most consistent evidence observed for all-cause mortality. Evidence for atherosclerotic cardiovascular events and cardiovascular mortality remains suggestive but limited by heterogeneity and few eligible studies.